Mengevaluasi Kembali Pandangan dalam Pemberantasan Tindak Pidana Korupsi di Masa Darurat Militer - Prysyazhnyuk, Olexandr; Shovkun, Yuriy; Korniienko, Maksym; Pashchenko, Yevhen; Nguindip, Nana Charles (Universitas Islam Negeri Antasari Banjarmasin, 2024)
This research addresses the fight against corruption under martial law in Ukraine, a relevant phenomenon as corruption poses a significant threat to national stability and democracy. The purpose of this study is to evaluate the effectiveness of anti-corruption legislation and infrastructure in the context of martial law. Using an analytical and dogmatic approach, the research combines legal analysis, secondary data, and semi-structured interviews with legal experts and civil society representatives, and the implementation of anti-corruption policies. The results show that while adequate anti-corruption laws and strategies exist, their implementation is hampered by weak inter-agency coordination, non-transparency, and lack of independent oversight. The implications of this study emphasize the importance of updating anti-corruption strategies and strengthening collaboration between state institutions and civil society to comprehensively address corruption. This study recommends updating anti-corruption strategies through the application of technology such as OSINT (Open Source Intelligence), stricter law enforcement, and strengthening collaboration between state institutions and civil society. Public education to build an anti-corruption culture is also identified as a strategic step.